2018
DOI: 10.1186/s12889-018-5544-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of HIV testing among adolescents 10–19 years in a post-conflict pastoralist community of Karamoja region, Uganda

Abstract: BackgroundAdolescents are a priority group in HIV prevention and treatment. This study sought to determine the prevalence and correlates of HIV testing services (HTS) among adolescents in the pastoralist post-conflict area of Karamoja sub region, Uganda.MethodsA cross sectional study of 1439 adolescents aged 10–19 years, attending nine public health facilities in five of the seven districts of Karamoja, was conducted between August to September 2016. Adolescents were consecutively selected and interviewed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 27 publications
9
29
6
Order By: Relevance
“…This finding was consistent with a study conducted in South Africa which showed that 32.7% of young females (aged 15-24 years) were tested for HIV [29]. However, the proportion of young women tested for HIV in this study was lower than studies conducted in Uganda (92%) [30], Karamoja region (81.8%) [31] and another study conducted in South Africa (60.1%) [16]. The reason for this difference might be the difference in the modalities the Uganda government used to reach the community for HIV counseling and testing (HCT).…”
Section: Discussionsupporting
confidence: 91%
“…This finding was consistent with a study conducted in South Africa which showed that 32.7% of young females (aged 15-24 years) were tested for HIV [29]. However, the proportion of young women tested for HIV in this study was lower than studies conducted in Uganda (92%) [30], Karamoja region (81.8%) [31] and another study conducted in South Africa (60.1%) [16]. The reason for this difference might be the difference in the modalities the Uganda government used to reach the community for HIV counseling and testing (HCT).…”
Section: Discussionsupporting
confidence: 91%
“…Although adolescents are at a greater risk of being infected, the testing rate is still low. In a similar study to assess the prevalence and correlates of HIV testing in Uganda, it was discovered that only 10.7% of adolescents aged 10–14 years had ever been tested for HIV [ 15 ]. Results of this study showed sex and age of the children and adolescents were not significantly associated with uptake of HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Although more children enrolled in school had been tested for HIV, this was not significant in the study. However, Ssebunya et al reported that adolescents with higher educational status were more likely to have been tested for HIV [ 15 ]. The study by Ssebunya et al included adolescents up to 19 years who needed no parental consent before getting tested for HIV [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations